2013
DOI: 10.1051/0004-6361/201322114
|View full text |Cite
|
Sign up to set email alerts
|

Doppler tomography of the circumstellar disk ofπAquarii

Abstract: Aims. The work is aimed at studying the circumstellar disk of the bright classical binary Be star π Aqr. Methods. We analysed variations of a double-peaked profile of the H α emission line in the spectrum of π Aqr that was observed in many phases during ∼40 orbital cycles in 2004−2013. We applied the discrete Fourier transform (DFT) method to search for periodicity in the peak intensity ratio (V/R). Doppler tomography was used to study the structure of the disk around the primary. Results. The dominant frequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 29 publications
2
46
1
Order By: Relevance
“…1 of Bjorkman et al 2002 and Fig. 3 of Zharikov et al 2013). The BeSS 3 database provides spectra obtained on 15 and 19 November 2013, bracketing our X-ray exposure date.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…1 of Bjorkman et al 2002 and Fig. 3 of Zharikov et al 2013). The BeSS 3 database provides spectra obtained on 15 and 19 November 2013, bracketing our X-ray exposure date.…”
Section: Discussionmentioning
confidence: 97%
“…In this context, it must be noted that the companion on the circular, 84.1 d orbit is certainly not a compact object (Bjorkman et al 2002;Zharikov et al 2013). Indeed, the large mass of the companion is incompatible with masses of white dwarves and neutron stars (Özel & Freire 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We employed Hα spectra from the Coudé Feed Telescope at the Kitt Peak National Observatory(KPNO), the Be Star Spectra Database (http://basebe.obspm.fr/basebe/), and 22 images from IUE to determine good orbital parameters for the primary. Zharikov et al (2013) found that excess Hα emission is located on the side of the disk facing the secondary. Since this is seen in other sdO objects, we searched for a hot companion in the FUV using cross-correlation templates for BD+28 4211 (T = 82 kK), BD+75 325 (T = 53 kK), and HD 49798 (T = 48 kK), but did not find a signature of the secondary.…”
Section: π Aquariimentioning
confidence: 99%